Apostasy by muslims in Malaysia: a legal analysis / Ashairi Fadli Mamat ...[et al.] - Mamat, Ashairi Fadli; Abdul Thalib, Nuratul Fakriah; Shahril Ridzwan Wan, Shamin; Abd Gani, Shazwani (2011)
The aim of this study is to find out the answer regarding the issue of apostasy amongst Muslims in this country. By virtue of the Federal Constitution, people are given their right to profess any religion of their own while on the other hand, some states in Malaysia have penalised Muslims who renounced Islamic faith and wish to profess other religion. This confers the meaning that Federal Constitution seems to restrict the right to religious liberty in the sense that freedom of religion in Malaysia is not absolute. Apart from that, the jurisdictional issues between Syariah Court and Civil Court also been discussed. It has been provided within the Federal Constitution that Islamic matters belong to the jurisdiction of state and most provisions in relation to apostasy are under the exclusive jurisdiction of Syariah Court. This consequently provides different approaches in each state in dealing with the issue of apostasy. This project paper makes an in-depth study of conflict of laws regarding freedom of religion and punishment for apostasy, the jurisdictional conflicts regarding apostasy between the Syariah Court and the Civil Court and also the non-uniformity of punishments for law of apostasy in Malaysia.